Modeling and molecular dynamics of aquaporin from an antarctic pseudomonas sp. strain AMS3 - Tuah, Muhairil Sulong; Latip, Wahhida; Ahmad Ridzwan, Ainur Yasmin; Balakrishnan, Samyuktha; Raja Abdul Rahman, Raja Noor Zaliha; Muhd Noor, Noor Dina; Mohamad Ali, Mohd Shukuri (Universiti Putra Malaysia Press, 2022)
Lightning is a naturally occurring phenomenon that involves a sudden electrostatic discharge caused by an imbalance between electrically charged cloud regions. Although lightning is visibly amazing, its impact can be dangerous and damaging, which many studies have carried out lightning-generated electric field measurements to assess the electrical discharge features. This study conducted the lightning-generated electric field measurement on the College of Engineering building rooftop at UNITEN from August 2019 to March 2020. A total of 115 negative lightning return strokes waveforms were recorded using a parallel plate antenna. A comparison was made between the data measured in the tropical and non-tropical regions, such as UTM, UPM, Sweden, USA, and Germany, in terms of the characteristic, mainly on the negative return strokes parameters. It was observed that data measured in the same region, either tropical or non-tropical, were consistent or almost similar. On the contrary, the results indicated a significant difference between these two regions on the negative return strokes parameters characteristics. The zero-to-peak and fast transition 10–90% rise time, as well as width dE/dt pulse at half peak value in the tropical region, were observed higher than the non-tropical region. Meanwhile, the zero-crossing time and slow front amplitude relative to the peak in the non-tropical region were averagely longer as compared to the tropical region. Therefore, dissimilarities in the characteristics of negative return stroke parameters could be attributed to the variation in the meteorological conditions, geographical locations, and climatic affection.